PENERAPAN MODEL PEMBELAJARAN EDUTAINMENT DALAM MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VIII.C DI UPTSMPN 34 MAKASSAR - Sabial Masani Hasan; Mustamin; Syarifa Raehana; Martini; Abdul Wahab (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This thesis discusses "The Application of the Edutaiment Learning Model in Improving Student Learning Achievement in Islamic Religious Education Subjects for Class VIII. C at the UPT SMPN 34 Makassar." The purpose of this study is to describe the application of the Edutaiment Learning Model in Improving Student Learning Achievement in Islamic Religious Education Subjects for Class VIII. C at the UPT SMPN 34 Makassar.This study is a Classroom Action Research (CAR) consisting of two cycles, where each cycle consists of two meetings. The subjects in this study were 30 students of class VIII. C at the UPT SMPN 34 Makassar. Data collection techniques in this study were observation, interviews, tests, and documentation. The data analysis techniques used in this study were using percentage calculation formulas and average values ​​(mean) for both the analysis of student activity sheet data and the completeness of student learning achievement.The results of the study on the application of the Edutainment Learning Model using Cycles I and II indicate that student learning outcomes in Cultural History for Class VIII.C at the UPT SMPN 34 Makassar increased in each cycle. This is evident in the student learning outcomes obtained in Cycles I and II. In Cycle I, 20 students achieved completion with an average score of 74.6, categorized as "good," or 66%. Meanwhile, in Cycle II, the number of students who completed the course increased to 26 with an average score of 86, categorized as "sufficient," or 86.66%.